ANALISIS SISTEM ANTRIAN DAN OPTIMALISASI PELAYANAN PADA CUSTOMER SERVICE DI STASIUN SOLO BALAPAN - Khoirul Anwar; Erni Widajanti; Sunarso Sunarso (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
This study aims to determine the queuing system for optimization of teller services at Bank Negara Indonesia, Slamet Riyadi Solo Branch Office. The data used in this study is a direct observation of the object of research / observation. The sampling technique uses the Leddy formula because the population cannot be known. The data analysis technique used is manual calculation using the queuing system formulas of many single-stage channels (multiple channel-single phase). The results of this study indicate that there are 2 service lines at Customer Service at Solo Balapan Station. Research hypothesis on Customer Service 1 at Solo Balapan Station that the service, and the average service time is not optimal with the average time to serve a customer > 5 minutes, or 5,6772 minutes, while the company's Standard Operating Procedure (SOP) < 5 minutes, so the researchers made calculations using the addition to 3 Customer Service and were only able to obtain optimal results ie < 5 minutes or 4,8276 minutes occurred in Customer Service 1. The average time customers spent waiting in the queue was 0,47712 minutes. Research hypothesis on Customer Service 2 at Solo Balapan Station that the service, and the average service time is optimal with the average time to serve a customer < 5 minutes, or 4,7952 minutes